Sulfotransferases in mediating the chlorophenol metabolism: Metabolites identification and metabolic characterization - Kai Yang; Guoqiang qin; RuoYong Jia; Haoqian Zhang; Qiangqiang Gan; Shao-You Lu; Jian-Jun Liu; Zhong-Ze Fang (Journal of Hazardous Materials Letters)
Chlorophenols (CPs) are persistent organic pollutants (POPs) widely detected in the natural environment. Sulfotransferases are a group of crucial phase II metabolic enzyme involved in the metabolism of endogenous and exogenous substances. This research aims to identify the metabolite and characterize the specific isoforms involved in the sulfonation of each CP. Recombinant enzyme assays and chemical inhibitors were used to characterize the primary SULT isoforms involved in the sulfonation of each CP. Our findings indicated that mono-sulfonate was identified in each incubation system. SULT1A1 predominated the sulfonation of monochlorophenol (MCP), SULT1A1, SULT1B1, and SULT1E1 emerged as the pivotal SULT isoforms mediating the sulfonation of 2,4-dichlorophenol (2,4-DCP), trichlorophenol (2,3,4-TCP), 2,4,6-trichlorophenol (2,4,6-TCP), and 3,4,5-trichlorophenol (3,4,5-TCP). Additionally, sulfonation of 2,4,5-trichlorophenol (2,4,5-TCP), 2,3,4,5-tetrachlorophenol (2,3,4,5-TECP), and 2,3,4,6-tetrachlorophenol (2,3,4,6-TECP) were primarily catalyzed by SULT1B1. Furthermore, SULT1B1 and SULT2A1 were the major isoforms involved in the sulfonation of 2,3,5,6-tetrachlorophenol (2,3,5,6-TECP) and pentachlorophenol (PCP). These results provide important insights into the metabolic elimination and toxicity of CPs from a novel perspective.